PREVALENCE OF MALE PELVIC DYSFUNCTION: RESULTS FROM THE TURKISH SOCIETY OF ANDROLOGY SEXUAL HEALTH STUDY GROUP - Kendirci, M.; Asci, R.; Cayan, S.; Yaman, O.; Orhan, I; Usta, M. F.; Kadioglu, A. (Wiley-Blackwell, 2012)
[Abstract Not Available]